Caesarean scar endometriosis: a case report - Cherrabi, Fatimazahra; Moukit, Mounir; Kouach, Jaouad; Rahali, Driss Moussaoui; Dehayni, Mohammed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Endometriosis is a common disorder in women of reproductive age but is rarely observed in abdominal scar after caesarean section. The authors report a case of 35-year-old woman referred for a painful lump at caesarean scar. Preoperative diagnosis of caesarean scar endometriosis was made on the basis of clinical examination and radiological imaging and confirmed histologically after large surgical excision of the mass. Increasing awareness of this rare entity among clinicians can help in early diagnosis and appropriate treatment.